IMPLEMENTASI SISTEM DETEKSI AKTIVITAS UMPAN DAN PENGUKURAN BERAT IKAN PADA ALAT PANCING BERBASIS IOT - Zaky, Muhammad; Nuraji, Diaz; Sholihah, Ratih Mar'atus (Universitas Lampung, 2025)
Fishing requires continuous monitoring to avoid missing the moment when a fish bites the bait. However, this traditional method is inefficient and exhausting. Therefore, this research develops an IoT-based smart fishing rod capable of automatically detecting bait activity and measuring the weight of caught fish. The system utilizes a Load Cell sensor and HX711 module to detect weight changes caused by fish bites and ESP8266 to send real-time notifications via Telegram Bot. Additionally, Fuzzy Logic Mamdani is implemented to determine the fish bite status based on weight changes and bite duration. System testing evaluates fish detection accuracy, notification transmission speed, and automatic fish weight-to-price conversion. The results indicate that the system can accurately detect fish bites, send notifications in under 3 seconds, and calculate fish prices with minimal error. With this system, anglers can efficiently monitor their fishing activity and determine their catch value automatically.